Femtosecond laser direct writing of pure three-dimensional fluorescent protein and its application to physiological pH sensing - Serien, Daniela; Kawano, Hiroyuki; Miyawaki, Atsushi; Sugioka, Koji; Narazaki, Aiko (Frontiers in Nanotechnology, 2023)
Femtosecond laser direct write (fs-LDW), a three-dimensional (3D) printing technology, is a promising method for creating microstructures made of proteins that retain their original function, enabling the development of complex biomimetic 3D microenvironments and versatile enhancements of medical microdevices. Fabrication using pure proteins via photoactivator-free femtosecond laser multiphoton crosslinking has recently been demonstrated This approach avoids the undesirable effects caused by the leaching of photoactivator molecules, and is thus regarded as suitable for biological applications. Here, we present the 3D fabrication of microstructures made of pure fluorescent protein variants, namely mScarlet, enhanced green fluorescent protein (EGFP), and enhanced blue fluorescent protein (EBFP2). Multicolor fluorescent microstructures are created using a sequential procedure with various precursors. We evaluate the dependence of fluorescence retention on fabrication parameters such as the total accumulated fluence. We demonstrate that microstructures made of EGFP can be applied to the detection of physiological pH changes. The results show that fs-LDW fabrication can broaden the application scope of fluorescent protein variants.